The Recurrence of Stricture in Postoperative Patients at Dr. Soetomo Hospital from 2013-2017: A Case-Control Study - I Dewa Gede Reza Sanjaya (Journal of Global Pharma Technology, 2020)
Background: Urethral stricture is one of urology disease that commonly occurs in men with the incidence increase above 54 years old. Urethroplasty was an effective management option for almost all types of stricture and remained as the gold standard. Recurrence of stricture is one of complication that can occur after operative treatment. Methods: A case-control study with secondary data of all patients treated and undergoing operative management of the anterior-posterior urethral stricture in Dr. Soetomo Hospital from January 2013 to December 2017. Diabetes mellitus, hypertension, urine culture, and previous history of sachse were as independent variables. The data described by the distribution table and continued by Chi-square test using the SPSS application. P-value